Efeito da suplementação de colostro enriquecido sobre as características morfológicas da mucosa intestinal de bezerros neonatos - Kindlein, Liris; Pauletti, Patricia; Bagaldo, Adriana Regina; Rodrigues, Ana Paula Oeda; Machado-Neto, Raul (Acta Scientiae Veterinariae, 2018)
Colostrum intake in neonatal calves is essential to obtain passive immunity and to influence metabolism, endocrine systems and the nutritional state. This study compares morphologic features of small intestine of calves fed a colostrum second meal at 12 hours of life with concentrations of immunoglobulin G (IgG) higher than 100mg mL -1 (fresh colostrum or artificially prepared with addition of lyophilized colostrum) or smaller than 30mg mL-1. Twenty-four Holstein calves were randomly grouped according to concentration of IgG intake at 12 hours of life: low (less than 30mg mL-1); high (more than 100mg mL-1); plus lyophilized colostrum (more than 120mg mL-1). Intestinal tissue samples were collected at 0, 10, 24 and 72 hours after birth to evaluate morphology in segments: duodenum; proximal, middle and distal jejunum and ileum by examined with a scanning electron microscope. Villi of all segments showed more organized and uniform morphology characteristics with age. Only the animals fed colostrum with more than 100mg mL-1 of IgG at 24 hours after birth still showed the distal jejunum villi disoriented and more united in comparison to the other ages and groups. Intake of lyophilized colostrum affected ileum morphology along experiment period. Higher concentration of immunologic and bioactive elements supplied for longer period of time could be responsible for promoting effects on the enterocytes. Use of colostrum with high IgG concentrations, with or without addition of lyophilized colostrum, influenced the precocity of the intestinal mucosa development in newborn calves, suggesting earlier maturation of the mucosa.